Strategi Kepala Sekolah dalam Meningkatkan Hubungan Harmonis Dengan Masyarakat Guna Peningkatan Mutu Sekolah - Haryato, Sigit; Sumayah, Sumayah; Waloyo, Teguh (Universitas Muhammadiyah Surakarta, 2024)
This research explains the harmonious relationship between the school principal, the school itself, and the community at SD IT Muhammadiyah Pangkalan Kerinci. The study aims to identify the strategies employed by the school principal in building harmonious relationship with the community. This research employs a qualitative descriptive method and an educational sociology approach. Data collection involves interviews, observations, and documentation. The research finding indicates that the school principal has successfully formulated effective strategies to build a harmonious relationship with the community through 1. Making collaboration the cornerstone of the principal's strategy, 2. Involving parents, teachers, and the community, 3. Mobilize the active role of teachers in strategic planning, and 4. Listen and create a positive learning environment. This study provides a profound understanding of the importance of a harmonious relationship between the school and the community in enhancing educational quality, as well as the pivotal role of the school principal in creating a positive educational environment.